Molecular Retrofitting Adapts a Metal–Organic Framework to Extreme Pressure - Kapustin, Eugene A. (ACS Cent Sci, 2017)
[Image: see text] Despite numerous studies on chemical and thermal stability of metal–organic frameworks (MOFs), mechanical stability remains largely undeveloped. To date, no strategy exists to control the mechanical deformation of MOFs under ultrahigh pressure. Here, we show that the mechanically unstable MOF-520 can be retrofitted by precise placement of a rigid 4,4′-biphenyldicarboxylate (BPDC) linker as a “girder” to afford a mechanically robust framework: MOF-520-BPDC. This retrofitting alters how the structure deforms under ultrahigh pressure and thus leads to a drastic enhancement of its mechanical robustness. While in the parent MOF-520 the pressure transmitting medium molecules diffuse into the pore and expand the structure from the inside upon compression, the girder in the new retrofitted MOF-520-BPDC prevents the framework from expansion by linking two adjacent secondary building units together. As a result, the modified MOF is stable under hydrostatic compression in a diamond-anvil cell up to 5.5 gigapascal. The increased mechanical stability of MOF-520-BPDC prohibits the typical amorphization observed for MOFs in this pressure range. Direct correlation between the orientation of these girders within the framework and its linear strain was estimated, providing new insights for the design of MOFs with optimized mechanical properties.